COMPARISON OF SERUM CREATINE KINASE ESTIMATION WITH SHORT TANDEM REPEATS BASED LINKAGE ANALYSIS IN CARRIERS AND AFFECTED CHILDREN OF DUCHENNE MUSCULAR DYSTROPHY - Hashim, Rizwan; Shaheen, Sajida; Ahmad, Suhaib; Sattar, Abdus; Khan, Farooq Ahmad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Duchenne Muscular Dystrophy (DMD) is an X-linked recessive lethal, genetic disorder characterised by progressive weakness of skeletal muscles which is untreatable and transmitted to males by carrier females. Advances in laboratory techniques now focus direct mutational analysis as the most reliable and indirect analysis based on Short Tandem Repeats (STR) based linkage analysis as feasible, inexpensive, and efficient method for carrier detection and prenatal diagnosis. The objective of this study was to compare the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic efficiency of Serum Creatine Kinase (SCK) with Short Tandem Repeats (STR) based linkage analysis in carriers and affected children of Duchenne Muscular Dystrophy. Methods: The study was carried out from Dec 2006 to Dec 2007 in families having index clinical cases of DMD who were referred from different hospitals for evaluation/workup of DMD. SCK was done as a preliminary investigation in all index cases. The PCR assay with STR based linkage analysis with Intron 44, 45, 49 and 50 of DMD gene were performed in all families. Six families were informative with Intron 44 of DMD gene and one family was non-informative with all four intronic markers of DMD. SCK analyses were done in all the family members and compared with PCR analysis in informative families. SCK was not performed on Chorionic villous sample (CVS) done for prenatal diagnosis of DMD, and CVS and non-informative family members were excluded from the study. Results: In carriers of DMD, the sensitivity and negative predictive value of SCK were 33.3%, and specificity and positive predictive were 100% with diagnostic efficiency of 50%. In affected cases of DMD the sensitivity and negative predictive value of SCK were 100%, and specificity and positive predictive were 91% and 88.8% respectively and diagnostic efficiency of 94.1%. Conclusion: The SCK is an excellent screening test for affected cases of DMD. For carrier identification we have to resort on PCR analysis so as to provide safer diagnostic tool for genetic counselling and prenatal diagnosis. Keywords: Duchenne muscular dystrophy, Creatine Kinase, Carrier detection, Short Tandem Repeats